Educational Applications and Comparative Analysis of Network Simulators: Protocols, Types, and Performance Evaluation - Nikolaos V. Oikonomou; Dimitrios V . Oikonomou (Journal of Engineering Research and Sciences, 2024)
This work explores the role of simulation in computer networks, discussing various network types, communication protocols, and the utilization of network simulators, with a focus on educational settings. We specifically analyze and compare five prominent network simulators: Cisco Packet Tracer, Riverbed Modeler Academic Edition, GNS3, NS-3, and Mininet. These tools are examined in terms of their functionality, user-friendliness, and suitability for educational purposes, assessing how they facilitate learning for students and trainees. The comparison extends to their operational capabilities, differences, effectiveness, and overall impact on networking education. The evaluation aims to highlight each simulator's strengths and weaknesses, providing insights into their practical applications in an academic context.
Keywords: Network Architecture; Network Simulation; Network Protocol; Emulator; Educational Technology; Performance Evaluation